Special Education and Individualized Academic Growth: A Longitudinal Assessment of Outcomes for Students With Disabilities. (April 2020) - Hurwitz, Sarah; Perry, Brea; Cohen, Emma D.; Skiba, Russell
This study examined the effectiveness of participating in special education on the academic outcomes of students with disabilities. A sample of 575 students from a large, urban school district were followed longitudinally as they transitioned between general and special education to evaluate whether receiving special education services was associated with improvements in academic trajectories. Using student fixed effects models of within-person change over time, individuals' performance on standardized tests were compared before, during, and/or after special education placement. Results indicate that test scores of students with disabilities improved after being enrolled in special education. Additionally, students exiting special education exhibited a sustained trajectory of academic growth, suggesting that participation in special education in this district was associated with enduring improvements over time.